Risk weighting for government bonds: Challenge for Italian banks - Dominik Meyland; Dorothea Schäfer (DIW Economic Bulletin, 2017)
Although banks are required to document their equity capital for loans, corporate bonds, and other receivables, they are currently exempted from the procedure when investing in government bonds: they enjoy an 'equity capital privilege.' As part of the Basel III regulatory framework redraft, the privilege may be eliminated in order to disentangle the default risks between sovereigns and banks. The present study examines how much additional equity capital the banks of the euro area's major nations would require if the equity capital privilege were eliminated. At nine billion euros, the estimates show the highest capital requirement for Italian banks. In comparison, French banks would only require additional capital of three billion euros and German banks would need just under two billion euros. Since eliminating the equity capital privilege would make the Italian state's consolidation efforts more difficult, it is advisable to risk weight newly purchased government bonds only or allow for long transition phases.
Keywords: G20; G28; G01; 330; Basel III; bank capital requirements; government bonds; banksovereign nexus